ENGLISH ROMANTICISM AND ITS DEVELOPMENT - Student of CSPU The English language theory and practice department Tojiyeva Sevinch Anvar qizi Scientific advisor: Kenjayeva Muxlisa Baxodir qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article aims at giving an overview on the whole romantic period. The start of the romantic period, the way it happened, the poets that helped to make this period shine, the background of the poets and the details of the romantic poetry that ruled this era – all of the aspects are described very elaborately in this article. The romantic age was established at the end of the eighteenth century and it lasted up to the 30’s of the nineteenth century. This romantic period replaced the neoclassical period where the classical poets like Alexander Pope made classical poetry famous among readers. Keywords: Romantic period, The development of English Romanticism, collaborative work, simplicity of everyday life, romantic ideology, neoclassical poetry, individual experience, intellectual sensibilities.